1995
DOI: 10.1515/cclm.1995.33.4.201
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Glomerular Filtration Rate by Identification of Sinistrin Kinetics

Abstract: Summary: A computer-based method of system identification and estimation of parameter variance for two-compartment models matched to dynamic sinistrin concentration profiles for the determination of glomerular filtration rate is described. Thereby a procedure for the judgment of the optimal sampling time horizon is presented. Since single-injection techniques are suspected of yielding systematic overestimation of the glomerular filtration rate, a method is demonstrated confirming that such a technique employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 29 publications
2
23
1
Order By: Relevance
“…In comparison to a two-or a four-compartmental modeling approach (data not shown), serum inulin kinetics could be best characterized by a three-compartment model. Model predictions for the serum compartment (V 1 : 3.5 Ϯ 0.3 l), the total inulin distribution volume (V inulin : 13.0 Ϯ 0.6 l), and the renal clearance were in accordance with previous findings (33)(34)(35). In particular, the model prediction of the renal clearance was in very good agreement with values as determined using the Cockcroft formula (21).…”
Section: Discussionsupporting
confidence: 87%
“…In comparison to a two-or a four-compartmental modeling approach (data not shown), serum inulin kinetics could be best characterized by a three-compartment model. Model predictions for the serum compartment (V 1 : 3.5 Ϯ 0.3 l), the total inulin distribution volume (V inulin : 13.0 Ϯ 0.6 l), and the renal clearance were in accordance with previous findings (33)(34)(35). In particular, the model prediction of the renal clearance was in very good agreement with values as determined using the Cockcroft formula (21).…”
Section: Discussionsupporting
confidence: 87%
“…The clearance of sinistrin (C Sinistrin ), a polyfructosan with identical clearance characteristics to inulin, is a validated reference method for the measurements of GFR before and after protein load (Inutest ® , Fresenius Pharma Austria, Linz, Austria). [16,24] The renal functional reserve was measured as the change in GFR after protein load. Time sequences of sinistrin injection, protein load, and measurements of variables have been described in detail in previous studies and are shown in Figure 1.…”
Section: Study Protocolmentioning
confidence: 99%
“…Time sequences of sinistrin injection, protein load, and measurements of variables have been described in detail in previous studies and are shown in Figure 1. [16,[22][23][24][25] Prior to examination, the patients were instructed to maintain a low sodium and protein diet for two days, to fast from midnight onward, and to collect their urine during the preceding 12 hr to assess compliance. On the day of the study, after a rest period of 30 minutes with a fluid intake of 0.5 l of light tea, the first clearance measurement started with the injection of 2500 mg sinistrin and baseline measurements were taken.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The above method, the general solution of the linear dynamic problem comprising both single-injection and constant-infusion experiments and a computational method for identification of the system constants have been developed previously with application to the kinetics of sinistrin as a marker of glomerular filtration (5). Although the same mathematical concept is applied here to the kinetics of jp-aminohippuric acid administered at low doses, the appropriateness of model-linearity and the pertinent protocol-and dose-requirements were investigated separately because of the combined action of glomerular filtration and tubular secretion and, consequently, the possibly concentration-dependent characteristics in the elimination of/7-aminohippuric acid.…”
Section: Introductionmentioning
confidence: 99%